Pengaruh Faktor Lingkungan Terhadap Kejadian Repeat Breeding Pada Sapi Perah - Nain Ufidiyati; Aqil Adyatama (Jurnal Javanica, 2026)
This study analyzed environmental factors influencing repeat breeding in dairy cattle in Ngablak District, Magelang Regency. A quantitative survey involved 336 productive cows purposively selected from 462 populations across 15 villages. Primary data were collected through questionnaires, observations, and interviews, while secondary data came from the Livestock Service. Risk factors analyzed included drinking water availability, barn design, water source, temperature, humidity, and barn cleanliness. Data were analyzed using Chi-Square and Odds Ratio (95% CI). The prevalence of repeat breeding was 27.67%. Significant factors were lack of ad libitum water (OR=2.59), absence of water source inside the barn (OR=22.5), high humidity, and poor cleanliness (OR=17.7). Barn design and temperature were not significant. High humidity and poor cleanliness triggered heat stress and postpartum infections, impairing reproduction. Suboptimal husbandry management is the main cause. Improvements to husbandry practices are essential.